ENGLISH TEACHING BASED ON INTERNATIONAL BACCALAUREATE PRIMARY YEARS PROGRAMME: TEACHERS’ BELIEFS AND PRACTICES - Heppy Mutammimah; Dewi Rochsantiningsih; Abdul Asib (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
This paper explores teachers’ beliefs in English teaching for young learners based on International Baccalaureate Primary Years Programe (IB PYP) and examines the interplay their beliefs on instructional practices. The researchers utilize a qualitative method and case study as a research design. Three English teachers at elementary school that implementing IB PYP in Surakarta participated in the study. Data is drawn from semi-structured interviews, observation and document analysis. For analyzing data, the researchers use an interactive model by Miles and Hubberman. The finding data indicates that most of teachers beliefs consistence with their instructional practices namely beliefs on learning objective, syllabus, classroom methods, instructional material and sources, media and assessment even thought the researcher find discrepancies namely teachers’ beliefs on lesson plan and classroom procedure. Based on this result, the researchers argue that reform in language teacher education need to address factors that hinder teachers from implementing instructions which aligns with their theoretical beliefs.ENGLISH TEACHING BASED ON INTERNATIONAL BACCALAUREATE PRIMARY YEARS PROGRAMME Teachers’ Beliefs And Practices